`Representing and Being Represented in Turn' – A Symposium on Hélène Landemore's Open Democracy. Issue 1 (2022) - Mansbridge, Jane; Cohen, Joshua; Cammack, Daniela; Stone, Peter; Achen, Christopher H.; Leib, Ethan J; Landemore, Hélène
No abstract available